Polymorphism of the Dopa-Decarboxylase Gene Modifies the Motor Response to Levodopa in Chinese Patients With Parkinson's Disease - Li, Lanting; Lin, Huixia; Hua, Ping; Yan, Lei; Dong, Hui; Li, Tan; Liu, Weiguo (Frontiers in Neurology, 2020)
Levodopa (L-DOPA) is the most effective drug for Parkinson’s disease (PD). However, the response to L-DOPA remains individually variable, which hampers the practical value of L-DOPA in the clinic. Genetic factors play a role in L-DOPA efficacy. This study explored the associations between polymorphisms and motor response to L-DOPA in Chinese patients with PD. A total of 51 Chinese PD patients were enrolled in this study. Patients underwent an acute L-DOPA challenge and were evaluated by the Unified Parkinson Disease Rating Scale (UPDRS) part Ⅲ at baseline and after L-DOPA administration. Subjects were genotyped for polymorphisms: rs921451 and rs3837091 in the DDC loci, rs3836790 in the SLC6A3 locus, rs4680 in the COMT locus, and rs1799836 in the MAOB locus. We found that patients carrying the DDC CT or TT genotype exhibited a better motor response to L-DOPA than patients with the DDC CC genotype, and there was still a significant difference after adjustment for the L-DOPA dose in the acute challenge. Improvement in the UPDRS Ⅲ subscores, including bradykinesia and axial symptoms, was significantly lower in patients with the DDC CC genotype than in patients with the CT or TT genotype. There were no significant associations between the motor response to L-DOPA and the rs3837091, rs3836790, rs4680, and rs1799836 variants. The DDC single nucleotide polymorphism rs921451 modulated the motor response to L-DOPA in Chinese PD patients. Our results suggested that DDC may be a modifier gene for the L-DOPA treatment response in PD.